Oil shocks, US economic uncertainty, and emerging stock markets. Issue 18 (24th October 2019) - Kwon, Dohyoung
ABSTRACT: This paper investigates the impacts of oil price shocks and US economic uncertainty on emerging equity markets within a structural VAR model. I find that both precautionary oil demand and US economic uncertainty shocks have significant negative effects on emerging stock returns, whereas aggregate demand shocks cause a sustained rise of the returns. In particular, the direct effects of oil shocks on emerging stock returns are amplified by the endogenous response of US economic uncertainty. Variance decomposition analysis shows that oil market fundamentals and US economic uncertainty are an important determinant of emerging equity returns, accounting for 35% and 24% of their long-term variations, respectively. The heterogeneous impacts of structural shocks on individual emerging markets, however, suggest that a well-diversified portfolio can be obtainable.